L’OACI au sein de l’ONU : le fonctionnalisme et ses applications - Sochor, Eugène (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1988)
The theory of functionalism is based on the notion that the cumulative effect of "functional" activities will tend to influence the political aims of governments towards more cooperation and fewer conflicts. This has not been the case in ICAO and it remains to be seen whether technical cooperation can transcend the vested national interests of states in the other aspects of civil aviation. Anything that is non-technical is likely to be political in nature, even when such issues come up before the ICAO Council, under the guise of technical problems. Any expectation that political and functional activities in aviation could be separated were dashed as soon as ICAO joined the United Nations System. As a consequence, it is bound to follow political positions which do not necessarily accord with its mandate and with the requirements of air transport.